INTERFACE DESIGN FOR CONTROL USING COMPUTER stoplight - Indrianto Indrianto Indrianto (STMIK Jakarta, 2004)
programs of a general nature only, such as: Word, Exel and the lainya.sebenarnya computercan be used widely as a controller or an external regulator, such as traffic light controllers,temperature measurement and the other.Computers communicate with the